Analisis Laporan Keuanganuntuk Mengevaluasi Kinerja Perusahaan (Case Study in PT. Anugerah Kartika Agro Surabaya) - Octaviyani, Nita; Mulyati, Diana Juni; Pratiwi, Ni Made Ida (Jurnal Dinamika Administrasi Bisnis, 2015)
In practice, the poultryworldincreasinglypopularamong peoplewithhousehold-scale enterprisescontinue to growinmany areas, whilethelarge-scale enterprisesis growingandable torun their businessmore efficiently. Thislarge-scale efforttriggermarketcompetitionsolargelivestockenterprisesdominatethe marketpriceor thesmall-scale farmersandpeopleselllivestockat a pricebelow the cost ofproduction. Performance ofthe companyplays an important rolein relation to thebusiness partnership, because thecompany's performance measurementbecomes veryimportant for managementto evaluatethe performance ofthe companyandplanningpurposesinthe future. In the course ofpoultry production facilities(sapronak) chickenwith the partnership(Inti-Plasma), the need foranalysisof financial statementsin ordertodeterminea company's financialpositionand the resultsthat have beenachievedbythe company.The financial statementsconsistofseveralparts, namely: Balance(Balance Sheet) andthe Profit/Loss(Income Statement). There are manyfinancial ratiosthatare madeaccording to the needsof analystscommonlyusedinfinancial analysis, including theliquidityratios, leverageratios, activity ratios andprofitabilityratios. The company's performancecan bemeasured using ameasuring instrumentcalledEVA(Ecomonic Value Added). Thus, by usingthe method of calculatingthefinancial statements analysisandperformance of the company, the resultisfinancial performance.AgroKartikaoptimalgraceandableto experiencea significantincrease in profits. Keywords: Financial Statement Analysis, Corporate Performance, Ratio Analysis